Microscopic Analysis of The Lung in Male Rat (Rattus Norvegicus) Exposed to Cigarettes Smoke - Adrien Jems Akiles Unitly; Nastiti Kusumorini; Srihadi Agungpriyono; Aryani Sismin Satyaningtijas; Arief Boediono (Universitas Syiah Kuala, 2018)
This research aimed to study on the microscopic changes of lungs in male rat that exposured to cigarette smoke. A factorial CRD with periode of treatment and sample collection was applied in this study. An exposure of cigarette smoke was carried out at 10 cigarettes/rat/day for 2.5 hours in an smoking chamber. Group N is untreated animals. Group 20d is exposed animals with cigarette smoke for 20 days consectitively and released from the cigarette smoke exposure for 20 days. Group 40d is exposed animals for 40 days and released from the cigarette smoke for 40 days. Group 60d is exposed animals for 60 days similar as above. Data collection was carried out twice : after exposure and after redeasing the cigarette smoke exposure. The parameters of observation microscopic analysis of lungs included weight wet of lung and change of lung histopathologic.The results show decreased weight wet of lung, increased number of blackish particulate deposits in the cytoplasm of alveoli at 40d and 60d considered as tar deposit, an increased activity of inflammatory cells of male rats after exposing which were unable to recover after releasing of cigarette smoke exposure.